An unusual presentation of gastric mucosa-associated lymphoid tissue (MALT) lymphoma following blunt abdominal trauma. Issue 10 (10th October 2019) - Nashed, Karim; Lai, Keith; Stevens, Tyler; Morris-Stiff, Gareth
Abstract : A 79-year-old woman presented to the emergency department following a motor vehicle collision. As part of her workup she underwent a CT scan which identified a large mass containing calcifications centred around the gastric antrum, and while being assessed she produced 500 mL of haematemesis. An endoscopy revealed an area of friable mucosa the nature of which was uncertain, and multiple biopsies revealed amyloid deposition and active Helicobacter pylori gastritis. Following review of imaging and pathology, a diagnosis of gastric mucosa-associated lymphoid tissue (MALT) lymphoma was established. She was treated with quadruple therapy for the H. pylori and at 6-month follow-up she is asymptomatic with repeat endoscopy revealing healing of the ulceration and no biopsy evidence of H. pylori or MALT.